2009
DOI: 10.1002/app.29580
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin‐anionic polysaccharide hydrogels: Synthesis, characterization, and interaction with some organic molecules (water pollutants, drugs, proteins)

Abstract: Hydrogel microparticles have been prepared through cocrosslinking of cyclodextrin and of anionic carboxymethyl or sulfopropyl pullulan with a new bifunctional reagent: 3-(glycidoxypropyl)trimethoxysilane. This reagent forms crosslinking both through grafting with the epoxy end on the OH polysaccharide and through hydrolysis and condensation of the methoxy silane groups from the other end. Samples of cyclodextrin/anionic polysaccharides with various amounts of crosslinking agent were prepared. Characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Source compounds present at high concentration. Due to their specific affinity toward drugs (Fenyvesi et al 1996;Vyas et al 2008;Mocanu et al 2009), they found their application for the sorption of non-biodegradable emerging contaminants, such as pharmaceuticals, which persits the traditional wastewater treatment and are usually detected in treated wastewater at very low concentrations.…”
Section: Removal Of Pharmaceuticals Using Cyclodextrin Bead Polymersmentioning
confidence: 99%
“…Source compounds present at high concentration. Due to their specific affinity toward drugs (Fenyvesi et al 1996;Vyas et al 2008;Mocanu et al 2009), they found their application for the sorption of non-biodegradable emerging contaminants, such as pharmaceuticals, which persits the traditional wastewater treatment and are usually detected in treated wastewater at very low concentrations.…”
Section: Removal Of Pharmaceuticals Using Cyclodextrin Bead Polymersmentioning
confidence: 99%
“…Although these beads usually outperformed activated carbon, it became clear that cyclodextrin polymer beads are too expensive for the removal of compounds present at high concentration. Due to their specific affinity toward drugs (Fenyvesi et al 1996;Vyas et al 2008;Mocanu et al 2009), they found their application for the sorption of non-biodegradable emerging contaminants, such as pharmaceuticals, which survive the traditional wastewater treatment and are usually detected in purified wastewater at very low concentrations.…”
Section: Removal Of Emerging Contaminants By Cyclodextrin Bead Polyme...mentioning
confidence: 99%
“…Hydrogels posses a highly hydrophilic character that may make the loading of hydrophobic drugs difficult and that limits their ability to control the release of the hydrophilic molecules (Alvarez-Lorenzo, Hiratani, & Concheiro, 2006;Kim, Bae, & Okano, 1992). Covalent binding of cyclodextrins (CDs) to the polymer networks has recently been seen as a promising way to overcome these drawbacks (Crini & Morcellet, 2002;dos Santos et al, 2009;Liu, Fan, Kang, & Sun, 2004;Mocanu, Mihai, LeCerf, Picton, & Moscovici, 2009;Rodriguez-Tenreiro, Alvarez-Lorenzo, Rodriguez-Perez, Concheiro, & Torres-Labandeira, 2006;Zhang, Xue, Gao, Huang, & Zhuo, 2008). The interest of CDs as integral components of hydrogels lies in that the capability of CDs to host drug molecules can be transmitted to the network, which enables the drug-CD affinity to play a relevant role in the loading and the release processes (Rodriguez-Tenreiro, AlvarezLorenzo, Rodriguez-Perez, Concheiro, & Torres-Labandeira, 2007a).…”
Section: Introductionmentioning
confidence: 99%